Single-component transparent dealcoholized organosilicon sealant as well as preparation method and application thereof
The curing speed is solved by using the mixing of polyalkoxy-terminated polydimethylsiloxane and white carbon black in a single-component transparent dealcoholized silicone sealant. It has high temperature and humidity resistance and transparency, and has achieved high strength and low modulus sealant, suitable for coating and bonding sealing of electronic appliances, and comply with environmental protection standards.
Patent Information
- Application Number
- CN202411588195.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
AI Technical Summary
The existing single-component transparent dehydrogenated silicone sealant has shortcomings in curing speed, high temperature and high humidity resistance, universal bonding, transparency and self-leveling performance, and the silicone ring content is high and not environmentally friendly, making it difficult to It takes into account both high strength and low modulus and does not comply with EU Reach regulations.
The polyalkoxy-terminated polydimethylsiloxane and white carbon black are fully mixed under heating and negative pressure conditions, combined with the combination of various functional crosslinking agents, and prepared a high bonding strength and low mold The curing process is optimized to improve performance by using specific preparation methods and additive ratios.
It achieves fast curing, good transparency, high temperature and humidity resistance and high strength sealant, suitable for coating and bonding sealing of electronic appliances, and meets environmental protection standards.
Smart Images

Figure BDA0005124836290000091 
Figure FDA0005124836280000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic silicon sealants, and in particular relates to a single-component transparent dealcoholized organic silicon sealant and a preparation method and application thereof. Background Art
[0002] Single-component transparent dealcoholized silicone sealant is increasingly used in the coating and three-proofing of electronic appliances, especially PCB boards, due to its excellent toughness, relatively wide operating temperature, good transparency, long-term stability and no corrosion.
[0003] CN102146208B discloses a method for preparing a transparent dealcoholized one-component room temperature vulcanized silicone rubber, which is characterized by comprising the following steps: vacuum stirring 80% to 90% of α, ω-dihydroxy polydimethylsiloxane, 1% to 15% of white carbon black reinforcing filler and 5% to 10% of alkane mixture plasticizer in a mixer at room temperature, then adding 1% to 5% of a siloxane crosslinking agent, vacuum stirring, then adding 0.01% to 2% of a titanate siloxane ester TiOSi catalyst, 0.01% to 3% of an organic tin catalyst and 0.01% to 5% of a silane coupling agent, vacuum stirring, discharging and packaging.
[0004] CN113462163B discloses a dealcoholized silicone rubber, specifically a dealcoholized high-strength transparent flowing silicone rubber and a preparation method thereof. The dealcoholized high-strength transparent flowing silicone rubber comprises, by weight, 100 parts of vinyl silicone oil, 5 to 30 parts of plasticizer, 15 to 30 parts of white carbon black, 0 to 6 parts of white carbon black treating agent, 2 to 5 parts of end-capping agent, 0.1 to 0.2 parts of platinum complex, 2 to 7 parts of cross-linking agent, 1 to 4 parts of coupling agent and 0.2 to 5 parts of catalyst.
[0005] CN109762511B provides a one-component dealcoholization room temperature vulcanized silicone sealant and its preparation method and application, which relates to the technical field of organic silicone sealants. The sealant comprises the following raw materials in parts by weight: 100 parts of polyalkoxy-terminated polydimethylsiloxane, 0-10 parts of dimethyl silicone oil, 2-6 parts of crosslinking agent, 5-15 parts of filler, 0.8-2.5 parts of tackifier, and 0.1-0.6 parts of tin catalyst. The one-component dealcoholization room temperature vulcanized silicone sealant of the present invention has the characteristics of good storage stability, adhesion, and yellowing resistance.
[0006] However, the single-component dealcoholized silicone sealants of current technology have one or more of the following problems:
[0007] (1) The curing speed is not fast enough to meet the production efficiency requirements of some customers.
[0008] (2) The high temperature and high humidity resistance is poor and cannot meet the use requirements in high temperature and high humidity environments.
[0009] (3) The universality of bonding is poor, and some components on the PCB board cannot be well bonded and protected, and are easy to fall off.
[0010] (4) The transparency is not good enough and cannot meet the transparency requirements of some customers.
[0011] (5) It is difficult to achieve high strength while maintaining low modulus. It is easy to break or cause parts to fall off when subjected to external interference or external force.
[0012] (6) The content of siloxane ring bodies D3 to D10 is relatively high, which is not environmentally friendly, does not comply with EU Reach regulations, and is not conducive to export.
[0013] (7) Poor self-leveling performance. Summary of the invention
[0014] In order to solve the above technical problems, especially the existing organic silicon sealant is difficult to take into account high bonding strength and low modulus, as well as self-leveling performance. The present invention provides a single-component transparent dealcoholization organic silicon sealant with excellent comprehensive performance and a preparation method thereof.
[0015] The first object of the present invention is to provide a one-component transparent dealcoholized organic silicone sealant, comprising the following components in parts by weight: 50 parts of polyalkoxy-terminated polydimethylsiloxane treated white carbon black base glue, 30-50 parts of polyalkoxy-terminated polydimethylsiloxane, 0.5-3 parts of a first cross-linking agent, 0.1-2 parts of a coupling agent, and 0.1-3 parts of a catalyst; the polyalkoxy-terminated polydimethylsiloxane treated white carbon black base glue is obtained by uniformly mixing polyalkoxy-terminated polydimethylsiloxane and white carbon black under elevated temperature and negative pressure conditions; the ... The terminal polydimethylsiloxane is at least one of product A, product B and product C obtained by the following preparation method: product A is obtained by reacting 100 parts by mass of dihydroxy polydimethylsiloxane, 2-4 parts by mass of a second crosslinking agent and 0.01-1 parts by mass of a catalyst; product B is obtained by reacting terminal vinyl silicone oil and trialkoxysilane at a molar ratio of alkenyl to trialkoxysilane of 1:1-1.1; product C is obtained by reacting terminal vinyl silicone oil and trialkoxysilane at a molar ratio of alkenyl to trialkoxysilane of 1:0.5-0.55.
[0016] Furthermore, in the preparation of the polyalkoxy-terminated polydimethylsiloxane treated white carbon black base rubber, white carbon black accounts for 20-30wt%; the temperature and negative pressure conditions are to increase the temperature to 100-130°C, and the negative pressure vacuum is -0.090 to 0.097MPa, such as a vacuum degree of -0.095MPa. Furthermore, the specific surface area of white carbon black is 170-300m 2 / g.
[0017] If the content of silica is too low, it is difficult to achieve sufficient shearing effect during the processing, resulting in unsatisfactory dispersion of silica and difficulty in achieving high light transmittance and good leveling performance; if the content of silica is too high, it is difficult to add, or the final base glue viscosity is too high, making adding difficult; a silica content of 20-30wt% of the base glue weight can achieve high light transmittance and good leveling performance without making the base glue viscosity too high.
[0018] Furthermore, in the preparation of product A, the viscosity of the dihydroxy polydimethylsiloxane is 750-5000 cps, the low-ring content is ≤0.5wt%, and the low-ring content refers to the total content of D3 to D10; the second cross-linking agent has the structural formula R1, R2, R3, and R4 are independently selected from alkoxy, alkyl, aryl, and alkenyl, provided that more than two of R1, R2, R3, and R4 are alkoxy. The catalyst is selected from acids (formic acid, acetic acid, sulfuric acid, hydrochloric acid, trifluoromethylbenzenesulfonic acid), bases (NaOH, KOH), and butanone oxime. When the catalyst is an acid or a base, the amount used is 0.01-0.05 parts by mass, and when the catalyst is butanone oxime, the amount used is 0.5-1 parts by mass. When the second cross-linking agent has 4 alkoxy groups, it is a tetrafunctional cross-linking agent; when the second cross-linking agent has 3 alkoxy groups, it is a trifunctional cross-linking agent; when the second cross-linking agent has 2 alkoxy groups, it is a difunctional cross-linking agent.
[0019] Furthermore, the dihydroxy polydimethylsiloxane is a component 1 with a viscosity of 750cps≤≤≤1000cps, a component 2 with a viscosity of 1000cps<≤1500cps, and a component 3 with a viscosity of 1500cps<≤5000cps in a mass ratio of 10-20:20-30:50-60; wherein the viscosity difference between component 1 and component 2 exceeds 500cps, and the viscosity difference between component 2 and component 3 exceeds 1500cps.
[0020] Furthermore, the second crosslinking agent is selected from at least one of tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, diisopropyldimethoxysilane and diisopropyldiethoxysilane. Preferably, the second crosslinking agent is a compound of a tetrafunctional crosslinking agent, a trifunctional crosslinking agent and a difunctional crosslinking agent in a mass ratio of 1-2:0.5-1:1-2. Among the above cross-linking agents, tetramethoxysilane, tetraethoxysilane, and tetraisopropoxysilane are tetrafunctional cross-linking agents; methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, and hexadecyltrimethoxysilane are trifunctional cross-linking agents; and dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, diisopropyldimethoxysilane, and diisopropyldiethoxysilane are difunctional cross-linking agents.
[0021] The inventor unexpectedly found that the silicone sealant obtained by compounding the second crosslinking agent in the above ratio can have the advantages of high bonding strength, low modulus and high temperature and high humidity aging resistance. The introduction of a four-functionality crosslinking agent increases the treatment effect on the filler, increases compatibility, and makes the leveling property better, but the dosage needs to be controlled. Too much dosage will lead to high modulus and reduced toughness. The introduction of a two-functionality crosslinking agent will reduce the modulus, but too much dosage will affect curing, making it impossible for the system to form a complete crosslinked network. So it is necessary to reasonably compound. Therefore, it is necessary to reasonably compound each crosslinking agent with different functionalities in a reasonable proportion to have high bonding strength, low modulus and weather resistance.
[0022] Furthermore, product A is obtained by a preparation method comprising the following steps: under an inert atmosphere, 100 parts by mass of dihydroxypolydimethylsiloxane and 2-4 parts by mass of a cross-linking agent are mixed uniformly, and then 0.01-1 parts by mass of a catalyst are added, the temperature is raised to 70-100° C., the reaction is carried out for 20-30 hours, low molecular weight volatile components are removed by vacuum, and the temperature is lowered to obtain product A.
[0023] Further, in the preparation of product B and product C, the viscosity of the terminal vinyl silicone oil is 1000-5000cps, and the low ring body content is ≤0.1wt%. Preferably, the terminal vinyl silicone oil is a component 4 with a viscosity of 1000-2000cps and a component 5 with a viscosity greater than 2000-5000cps, which is compounded in a mass ratio of 1-2:1-2; the viscosity difference between component 4 and component 5 exceeds 2000cps. The structural formula of the trialkoxysilane is HSi(OR5)(OR6)(OR7), and R5, R6, and R7 are independently selected from methyl, ethyl, and isopropyl. For example, the trialkoxysilane is selected from at least one of trimethoxysilane, triethoxysilane, methoxydiethoxysilane, dimethoxyethoxysilane, and triisopropoxysilane.
[0024] Furthermore, in the preparation of product B and product C, the reaction of terminal vinyl silicone oil and trialkoxysilane is carried out in the presence of a Pt catalyst, and the Pt catalyst is selected from at least one of chloroplatinic acid, supported platinum, platinum acetylacetonate, platinum tetrachloride, and a Custer catalyst, and the amount of the Pt catalyst is such that the Pt content in the system is 10-100 ppm, preferably 20-50 ppm.
[0025] Furthermore, the first crosslinking agent is selected from at least one of tetramethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, polymethyl orthosilicate and polyethyl orthosilicate; the coupling agent is selected from KH550, KH560, KH792, KH602, KH570, KH540, dynasylan @ 1146. At least one of 1,3,5-tris(trimethoxysilylpropyl)polyisocyanate; the catalyst is selected from dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dimethyltin dineodecanoate, chelated organic tin, tetrabutyl titanate, tetratert-butyl titanate, 9000 Titanate Chelate, 726 at least one of titanate chelates.
[0026] Preferably, the coupling agent is a product of mixing KH550 and KH560 in a mass ratio of 1-2:1-2 at 70-120° C. in an environment isolated from moisture.
[0027] Optionally, the one-component transparent dealcoholized silicone sealant of the present invention further comprises some auxiliary agents, such as a plasticizer, a color paste, and a fluorescent indicator.
[0028] The one-component transparent dealcoholized organosilicon sealant composition provided by the present invention is suitable for shallow coating and sealing bonding with a thickness of less than 6 mm. After coating, it is cured in an environment with a temperature of 15 to 35° C. and a humidity of 30 to 85% RH to achieve rapid curing. The organosilicon sealant of the present invention is particularly suitable for shallow coating and sealing bonding with a thickness of less than 3 mm. After coating, it is cured in an environment with a temperature of 25 to 35° C. and a humidity of 50 to 85% RH to achieve faster curing.
[0029] The composition of the present invention can generally meet most application requirements by curing under the temperature and humidity conditions of 25°C and 50%RH, achieving a curing depth close to or even exceeding 1mm in 2 hours; and faster curing can be achieved by increasing the ambient temperature and humidity. However, the temperature and humidity should not be too high, otherwise the curing will be too fast, resulting in the small molecules generated during the condensation reaction not being released in time, and gathering inside to form bubbles, which in turn affects the use effect. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further explained below with specific implementation methods.
[0031] The reagents used in the examples of the present invention are all commercially available. Table 1 shows the model of dihydroxy polydimethylsiloxane (107 glue) used in the present invention, and Table 2 shows the model of vinyl-terminated silicone oil used in the present invention.
[0032] Table 1 Dihydroxy polydimethylsiloxane models
[0033] Brand Viscosity(cps) D3~D10 content supplier H48V5000 5000 ≤0.5% Jiangxi Lanxing Star Silicone Co., Ltd. HP48V750 750 ≤0.1% Jiangxi Lanxing Star Silicone Co., Ltd. OP48V1500 1500 ≤0.03% Jiangxi Lanxing Star Silicone Co., Ltd. HP48V5000 5000 ≤0.1% Jiangxi Lanxing Star Silicone Co., Ltd.
[0034] Table 2 Vinyl-terminated silicone oil models
[0035] Brand Viscosity(cps) D3~D10 content supplier L621V1000 1000 <0.1% Jiangxi Lanxing Star Silicone Co., Ltd. L621V5000 5000 <0.1% Jiangxi Lanxing Star Silicone Co., Ltd.
[0036] Tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane: industrial grade, Hangzhou Guibao Chemical Co., Ltd.; KH550, KH560: industrial grade, Jingzhou Jianghan Fine Chemical Co., Ltd.; 726, 9000: Guangzhou Jianyi Chemical Import & Export Co., Ltd.; Hydrophobic silica: R974, 812S, Evonik Degussa China Co., Ltd.; Coupling agent dynasylan @ 1146: Evonik Degussa China Co., Ltd.; butanone oxime, trimethoxysilane, chloroplatinic acid hexahydrate: Aladdin chemical reagent procurement platform.
[0037] Example 1
[0038] (S1) 10 parts by weight of HP48V750, 30 parts by weight of OP48V1500 and 60 parts by weight of HP48V5000 are added to a high-speed stirring kettle equipped with a nitrogen system, a vacuum system and a heating and cooling system, and then 3 parts by weight of a second cross-linking agent (tetramethoxysilane, methyltrimethoxysilane and dimethyldimethoxysilane are compounded in a mass ratio of 2:1:2) are added, and the mixture is fully mixed. Then, 0.5 parts by weight of butanone oxime is added, and under the protection of dry nitrogen, stirring is continued, and the temperature is gradually raised to 100°C, and the reaction is carried out for 24 hours. Finally, low molecular weight is removed by vacuum at a temperature of 120°C, and then the temperature is cooled to room temperature to obtain product A.
[0039] (S2) Add 70 parts by weight of product A into a high-speed stirring kettle equipped with a heating and vacuuming device, add a total of 30 parts by weight of hydrophobic silica R974 in portions, and disperse evenly; then heat to 120°C, stir for 180 minutes at a negative pressure of -0.095 MPa and a rotation speed of 600 rpm; isolate from moisture and cool to room temperature to obtain a base rubber.
[0040] (S3) 50 parts by weight of the base rubber is added to a high-speed stirring kettle with a heating and vacuuming device, 30 parts by weight of the product A is added thereto, mixed evenly, and then 2 parts by weight of the first crosslinking agent vinyl trimethoxy silane, 0.5 parts by weight of KH550, and 1.2 parts by weight of 726, isolating moisture, mixing evenly, and degassing to obtain a sealant composition.
[0041] Example 2
[0042] The other conditions are the same as those in Example 1, except that in step (S1), the second cross-linking agent is a compound of tetramethoxysilane, methyltrimethoxysilane and dimethyldimethoxysilane in a mass ratio of 2:0.5:1.
[0043] Example 3
[0044] The other conditions are the same as those in Example 1, except that in step (S1), the second cross-linking agent is 2.25 parts by weight of tetramethoxysilane.
[0045] Example 4
[0046] The other conditions are the same as those in Example 1, except that in step (S1), the second crosslinking agent is 3 parts by weight of methyltrimethoxysilane.
[0047] Example 5
[0048] The other conditions are the same as those in Example 1, except that in step (S1), the second cross-linking agent is a compound of tetramethoxysilane and dimethyldimethoxysilane in a mass ratio of 1:1.
[0049] Example 6
[0050] The other conditions are the same as those in Example 1, except that in step (S3), the amount of product A used is 50 parts by weight.
[0051] Example 7
[0052] The other conditions are the same as those in Example 1, except that in step (S3), the coupling agent is the product of the reaction of KH550 and KH560 at a ratio of 1.5:1 at 80°C in an isolated moisture environment.
[0053] Example 8
[0054] The other conditions are the same as those in Example 1, except that in step (S2), the amount of product A is 80 parts by weight, and the amount of hydrophobic silica R974 is 20 parts.
[0055] Example 9
[0056] (S1) 50 parts by weight of L621V1000 and 50 parts by weight of L621V5000 are added to a high-speed stirring kettle equipped with a nitrogen system, a vacuum system and a heating and cooling system, and then trimethoxysilane is added in an equal molar ratio to vinyl, and 20 ppm of chloroplatinic acid hexahydrate is added, and the reaction is carried out under nitrogen protection for 24 hours. Finally, low molecular weight is removed by vacuum at a temperature of 120°C, and then the temperature is cooled to room temperature to obtain product B.
[0057] (S2) Add 75 parts by weight of product B into a high-speed stirring kettle equipped with a heating and vacuuming device, add a total of 25 parts by weight of hydrophobic silica R974 in batches, and disperse evenly; then heat to 150°C, stir for 120 minutes at a negative pressure of -0.097 MPa and a rotation speed of 800 rpm; isolate moisture and cool to room temperature to obtain a base rubber.
[0058] (S3) 50 parts by weight of the base glue is added to a high-speed stirring kettle with a heating and vacuuming device, and 40 parts by weight of the product B component is added thereto, mixed evenly, and then 2 parts by weight of vinyl trimethoxy silane, 0.5 parts by weight of the product of the moisture-proof reaction of KH550 and KH560 in a ratio of 2:1 at 80°C, and 0.7 parts by weight of 9000, isolate moisture, mix evenly, and degas to obtain the sealant composition of Example 7.
[0059] Example 10
[0060] The other conditions are the same as those in Example 7, except that in step (S1), trimethoxysilane is added in an amount 0.5 times the molar amount of the vinyl group, and finally product C is obtained. In step (S3), product B is replaced by product C.
[0061] Comparative Example 1
[0062] The other conditions are the same as those in Example 1, except that in step (S3), the first crosslinking agent vinyltrimethoxysilane is not added.
[0063] Comparative Example 2
[0064] (S1) 10 parts by weight of HP48V750, 30 parts by weight of OP48V1500 and 60 parts by weight of HP48V5000 are added to a high-speed stirring kettle equipped with a nitrogen system, a vacuum system and a heating and cooling system, and then 3 parts by weight of a second cross-linking agent (tetramethoxysilane, methyltrimethoxysilane and dimethyldimethoxysilane are compounded in a mass ratio of 2:1:2) are added, and the mixture is fully mixed. Then, 0.5 parts by weight of butanone oxime is added, and under the protection of dry nitrogen, stirring is continued, and the temperature is gradually raised to 100°C, and the reaction is carried out for 24 hours. Finally, low molecular weight is removed by vacuum at a temperature of 120°C, and then the temperature is cooled to room temperature to obtain product A.
[0065] (S2) Add 80 parts by weight of product A into a high-speed stirring kettle equipped with a heating and vacuuming device, add a total of 20 parts by weight of hydrophobic silica R974 in batches, and disperse evenly; then heat to 120°C, stir for 180 minutes at a negative pressure of -0.095 MPa and a rotation speed of 600 rpm; isolate moisture and cool to room temperature to obtain a base rubber.
[0066] (S3) 90 parts by weight of product A was added to a high-speed stirring kettle with a heating and vacuuming device, 10 parts by weight of hydrophobic white carbon black R974 was added, mixed evenly, and then 2 parts by weight of the first crosslinking agent vinyl trimethoxy silane, 0.5 parts by weight of KH550, 1.2 parts by weight of 726, isolating moisture, mixing evenly, and degassing to obtain a sealant composition.
[0067] That is, compared with Example 1, the raw materials used in Comparative Example 1 are the same, but the white carbon black is not mixed with the product in advance to prepare the base rubber, but is directly mixed with Product A.
[0068] Application Examples
[0069] The following performance tests were performed on the organic silicone sealants obtained in the above examples and comparative examples. The results are shown in Table 3.
[0070] Tensile strength: According to GB / T 528-2009 (Type 2 specimen)
[0071] 100% tensile modulus: According to GB / T 528-2009 (Type 2 specimen)
[0072] The depth of cure is tested at 23±2℃, 50±5%RH.
[0073] Light transmittance: The examples and comparative examples were cured at 23±2°C and 50±5% RH for 7 days to prepare flat and uniform samples with a thickness of 2±0.1 mm. The optical properties were tested using the full transmission mode on an X-Rite visible spectrophotometer CI7800.
[0074] Leveling performance: visual inspection.
[0075] High temperature and high humidity resistance: After preparing samples of the embodiment and comparative example according to the above tensile strength and hardness standards and curing for a sufficient time, put them into a constant temperature and humidity chamber at 85°C and 85%RH for aging for 1000h, take out the samples, cure them at 23±2°C and 50±5%RH for 24h, and then test the tensile strength and hardness according to the relevant standards. Performance retention rate = performance of the sample after aging / initial performance of the sample × 100%.
[0076] Table 3 Performance test of one-component transparent dealcoholized silicone sealant
[0077]
[0078] It can be seen from the data in Table 1 that the one-component silicone sealant prepared by the present invention has excellent comprehensive performance, fast curing speed and deep curing depth, good light transmittance, high mechanical properties and low modulus, excellent bonding strength and long-term high temperature and high humidity resistance, and is suitable for coating and bonding sealing of electronic appliances, especially PCB boards. The present invention obtains a multi-alkoxy-terminated polydimethylsiloxane by compounding a cross-linking agent, and then mixes it with white carbon black to obtain a base glue, which can achieve the purpose of high strength and low modulus while achieving good leveling performance.
[0079] Comparative Example 1 did not add the first crosslinking agent, resulting in a significant decrease in the resistance to double 85; and Comparative Example 2 was found to have gelled after being stored at room temperature for 5 months and could not be used normally. The other embodiments can be stored at room temperature for more than 12 months, and the performance data does not differ from the initial state by more than 20%. Comparative Example 2 lacks the step of preparing the base glue using high shear, and directly adds white carbon black, resulting in the inability to achieve self-leveling, and the modulus is high, and the resistance to double 85 is also affected to a certain extent.
Claims
1. A one-component transparent dealcoholized silicone sealant, characterized in that: The invention comprises the following components in parts by weight: 50 parts of polyalkoxy-terminated polydimethylsiloxane treated white carbon black base rubber, 30-50 parts of polyalkoxy-terminated polydimethylsiloxane, 0.5-3 parts of a first crosslinking agent, 0.1-2 parts of a coupling agent, and 0.1-3 parts of a catalyst; the polyalkoxy-terminated polydimethylsiloxane treated white carbon black base rubber is obtained by uniformly mixing polyalkoxy-terminated polydimethylsiloxane and white carbon black under elevated temperature and negative pressure conditions; the alkoxy-terminated polydimethylsiloxane is prepared by the following method At least one of product A, product B and product C is obtained by the method: product A is obtained by reacting 100 parts by mass of dihydroxy polydimethylsiloxane, 2-4 parts by mass of a second cross-linking agent and 0.01-1 parts by mass of a catalyst; product B is obtained by reacting terminal vinyl silicone oil and trialkoxysilane at a molar ratio of alkenyl to trialkoxysilane of 1:1-1.1; product C is obtained by reacting terminal vinyl silicone oil and trialkoxysilane at a molar ratio of alkenyl to trialkoxysilane of 1:0.5-0.
55.
2. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: In the preparation of the polyalkoxy-terminated polydimethylsiloxane treated white carbon black base rubber, white carbon black accounts for 20-30wt%; the temperature and negative pressure conditions are to increase the temperature to 100-130°C, and the negative pressure vacuum is -0.090 to 0.097MPa; further, the specific surface area of white carbon black is 170-300m 2 / g.
3. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: In the preparation of product A, the viscosity of the dihydroxy polydimethylsiloxane is 750-5000cps, the low-ring content is ≤0.5wt%, and the low-ring content refers to the total content of D3 to D10; the second cross-linking agent has the structural formula R1, R2, R3, and R4 are independently selected from alkoxy, alkyl, aryl, and alkenyl, provided that two or more of R1, R2, R3, and R4 are alkoxy; the catalyst is selected from acids (formic acid, acetic acid, sulfuric acid, hydrochloric acid, trifluoromethylbenzenesulfonic acid), bases (NaOH, KOH), and butanone oxime; Furthermore, when the catalyst is an acid or a base, the amount used is 0.01-0.05 parts by mass, and when the catalyst is butanone oxime, the amount used is 0.5-1 parts by mass.
4. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: The dihydroxy polydimethylsiloxane is compounded with component 1 having a viscosity of 750cps≤≤≤1000cps, component 2 having a viscosity of 1000cps<≤1500cps, and component 3 having a viscosity of 1500cps<≤5000cps in a mass ratio of 10-20:20-30:50-60; wherein the viscosity difference between component 1 and component 2 exceeds 500cps, and the viscosity difference between component 2 and component 3 exceeds 1500cps.
5. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: The second crosslinking agent is selected from at least one of tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, diisopropyldimethoxysilane and diisopropyldiethoxysilane.
6. The one-component transparent dealcoholized silicone sealant according to claim 5, characterized in that: The second crosslinking agent is a compound of a tetrafunctional crosslinking agent, a trifunctional crosslinking agent, and a difunctional crosslinking agent in a mass ratio of 1-2:0.5-1:1-2.
7. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: Product A is prepared by a preparation method comprising the following steps: under an inert atmosphere, 100 parts by mass of dihydroxypolydimethylsiloxane and 2-4 parts by mass of a cross-linking agent are uniformly mixed, 0.01-1 parts by mass of a catalyst are added, the temperature is raised to 70-100° C., the reaction is performed for 20-30 hours, low molecular weight volatile components are removed in vacuo, and the temperature is lowered to obtain product A.
8. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: In the preparation of product B and product C, the viscosity of the vinyl-terminated silicone oil is 1000-5000 cps, and the low-ring content is ≤0.1wt%; Preferably, the vinyl-terminated silicone oil is a compound of component 4 with a viscosity of 1000-2000cps and component 5 with a viscosity greater than 2000-5000cps in a mass ratio of 1-2:1-2; the viscosity difference between component 4 and component 5 is more than 2000cps; the structural formula of the trialkoxysilane is HSi(OR5)(OR6)(OR7), and R5, R6, and R7 are independently selected from methyl, ethyl, and isopropyl.
9. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: In the preparation of product B and product C, the reaction of terminal vinyl silicone oil and trialkoxysilane is carried out in the presence of a Pt catalyst, wherein the Pt catalyst is selected from at least one of chloroplatinic acid, supported platinum, platinum acetylacetonate, platinum tetrachloride, and a Custer catalyst, and the amount of the Pt catalyst is such that the Pt content in the system is 10-100 ppm, preferably 20-50 ppm.
10. The one-component transparent dealcoholized silicone sealant according to claim 1, characterized in that: The first crosslinking agent is selected from at least one of tetramethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, polymethyl orthosilicate and polyethyl orthosilicate; the coupling agent is selected from KH550, KH560, KH792, KH602, KH570, KH540, dynasylan @ 1146. At least one of 1,3,5-tris(trimethoxysilylpropyl)polyisocyanate; the catalyst is selected from dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dimethyltin dineodecanoate, chelated organic tin, tetrabutyl titanate, tetratert-butyl titanate, 9000 Titanate Chelate, 726 at least one of titanate chelates; Preferably, the coupling agent is a product of mixing KH550 and KH560 in a mass ratio of 1-2:1-2 at 70-120° C. in an environment isolated from moisture.
Citation Information
Patent Citations
Method for preparing transparent dealcoholized single-component room temperature vulcanized silicone rubber
CN102146208B
A one-component, alcohol-free, room-temperature vulcanizing silicone sealant and its preparation method
CN109762511B
A high-strength transparent flowable silicone rubber with alcohol removal and its preparation method
CN113462163B